Analysis of Human Resource Capabilities in Improving Discipline as a Form of Apparatus Professionalism in The Dau SubDistrict Office, Malang Regency - Wando Erlangga; R.Y Susanto; Fitria Setyaningrum; Fendiyatmi Kusufa (IRDH International Journal of Social Sciences & Humanities, 2026)
This study aims to evaluate employee capability in improving discipline as a form of staff professionalism at the Dau District Office, Malang                     Regency. Employee capacity includes knowledge, skills, and work attitudes that play an important role in task implementation and public service delivery. Employee discipline is a key indicator of professionalism, particularly reflected in compliance with work regulations, punctuality, and responsibility in carrying out duties. This study employs a qualitative approach using a descriptive method. Data were collected through interviews, observations, and documentation involving employees at the Dau District Office. The findings indicate that human resource capability at the Dau District Office is generally adequate; however, several challenges remain in the implementation of work discipline, such as limited supervision and inconsistency in enforcing regulations. To enhance employee professionalism, measures that can be taken include strengthening human resource capacity, improving discipline training, and conducting continuous performance evaluations. Through this study, it is expected to provide input for local government in improving the quality of human resources and public services.